2016
DOI: 10.1248/cpb.c15-00940
|View full text |Cite
|
Sign up to set email alerts
|

Poly-ion Complex of Chondroitin Sulfate and Spermine and Its Effect on Oral Chondroitin Sulfate Bioavailability

Abstract: Chondroitin sulfate (CS) has been accepted as an ingredient in health foods for the treatment of symptoms related to arthritis and cartilage repair. However, CS is poorly absorbed through the gastrointestinal tract because of its high negative electric charges and molecular weight (MW). In this study, poly-ion complex (PIC) formation was found in aqueous solutions through electrostatic interaction between CS and polyamines-organic molecules having two or more primary amino groups ubiquitously distributed in na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…In addition to MW, the high charge density and hydrophilicity of SPs also significantly affect their bioaccessibility/bioavailability and health effects (Baici et al., 1992). Recent studies have attempted to reduce the negative charge and hydrophilicity of SPs through electrostatic interaction and conjugation effect, thereby increasing their oral bioavailability and enhancing the health effects (Ge et al., 2016; Xiao, Fei, et al., 2014. In particular, CS possessed nearly neutral surface charge after it was combined with polyamines through electrostatic interaction, which remarkably improved its oral bioavailability (Ge et al., 2016).…”
Section: Effect Of Processing Techniques On the Structural Characteristics And Health Effects Of Spsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to MW, the high charge density and hydrophilicity of SPs also significantly affect their bioaccessibility/bioavailability and health effects (Baici et al., 1992). Recent studies have attempted to reduce the negative charge and hydrophilicity of SPs through electrostatic interaction and conjugation effect, thereby increasing their oral bioavailability and enhancing the health effects (Ge et al., 2016; Xiao, Fei, et al., 2014. In particular, CS possessed nearly neutral surface charge after it was combined with polyamines through electrostatic interaction, which remarkably improved its oral bioavailability (Ge et al., 2016).…”
Section: Effect Of Processing Techniques On the Structural Characteristics And Health Effects Of Spsmentioning
confidence: 99%
“…Recent studies have attempted to reduce the negative charge and hydrophilicity of SPs through electrostatic interaction and conjugation effect, thereby increasing their oral bioavailability and enhancing the health effects (Ge et al., 2016; Xiao, Fei, et al., 2014. In particular, CS possessed nearly neutral surface charge after it was combined with polyamines through electrostatic interaction, which remarkably improved its oral bioavailability (Ge et al., 2016). CS conjugation with α‐linolenic acid could improve its hydrophobicity, which could produce a positive synergistic effect on its anti‐inflammation and antiatherosclerosis effects (Xiao et al., 2014).…”
Section: Effect Of Processing Techniques On the Structural Characteristics And Health Effects Of Spsmentioning
confidence: 99%
“…If the two layers were thoroughly mixed again using a vortex mixer, the original PIC suspension could be restored. Morphological characterization of the PIC suspension from heparin (10 mg/mL) and 10 mM SPM showed that it was spherical in shape and in a micrometer size range ( Figure 1 B), correlating closely with the particle size (0.57 ± 0.25 μm) measured by dynamic light scattering ( Table 1 ) [ 22 ].
Figure 1 PIC formation efficiency was influenced by mixing concentration ratio of heparin and polyamines, the molecular weight of heparin.
…”
Section: Resultsmentioning
confidence: 66%
“…Equivalent volumes of solutions of heparin and polyamines were then mixed to generate the PIC. The PIC formation efficiency, effect of pH value on the stability of PIC, determination of particle size and ζ-potential, surface structure analysis were evaluated as described previously [ 22 ]. Low molecular weight heparin was obtained by photochemical depolymerization with titanium dioxide (TiO 2 ) [ 23 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation